Influenza A Viruses in Poultry: A Condensed Review - Burgos, Sigfrido; Burgos, Sergio A. (International Journal of Poultry Science, 2007)
Influenza A viruses are comprised of 8 negative-sense RNA segments coding 11 proteins; divided into low and high pathogenicity. They use recombination, deletions and insertions to escape immune system detection. Its epidemiology is defined by interactions between the host, agent and environment. Wild birds are their natural reservoirs; they replicate in the intestinal tract, shed in faeces and transmitted by faecal-oral transmission. They attach to host cells by binding to sialosaccharides on the host cell surface, predominantly to type II pneumocytes, alveolar macrophages and nonciliated cuboidal epithelial cells in terminal bronchioles. High mortality rates of 61% in humans and 90-100% in poultry are seen.